43.7k views
1 vote
Rewrite in simplest rational exponent form √x • 4√x. Show each step of your process.

User Tejeshree
by
6.0k points

1 Answer

2 votes


\bf ~\hspace{7em}\textit{rational exponents} \\\\ a^{( n)/( m)} \implies \sqrt[ m]{a^ n} ~\hspace{10em} a^{-( n)/( m)} \implies \cfrac{1}{a^{( n)/( m)}} \implies \cfrac{1}{\sqrt[ m]{a^ n}} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ √(x)\cdot 4√(x)\implies x^{(1)/(2)}\cdot 4x^{(1)/(2)}\implies 4x^{(1)/(2)}x^{(1)/(2)}\implies 4x^{(1)/(2)+(1)/(2)}\implies 4x^{(2)/(2)}\implies 4x

User DEKKER
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.